Dynamics of Growth and Stability in the Islamic Financial Services Industry on ECA, GCC, MENA, SSA, and EAP - Wahyudi, Heru; Lestari, Winda Rika; Said, Usamah Bin; Leny, Sandra Mei; Awaluddin, Imam (International Journal of Economics and Financial Issues, 2025)
The Islamic Financial Services Industry is experiencing significant growth despite the global economic challenges, such as inflation, geopolitical tensions, and rising global debt. The stability of Islamic finance is becoming increasingly crucial in ensuring the resilience of the global financial system. However, there is still a research gap in empirically evaluating the role of Islamic financial instruments such as Sukuk (Islamic Bonds), Takaful, and Islamic Fund, on the growth and stability of IFSI. Therefore, this study aims to analyse the effect of these three instruments on IFSI growth and evaluate the variation of their impact across regions. Using panel data regression method for the period 2017-2023, this study focuses on five main regions, namely Europe and Central Asia (ECA), Gulf Cooperation Council (GCC), Middle East and North Africa (MENA), Sub-Saharan Africa (SSA), and East Asia and the Pacific (EAP). The results showed that Sukuk, Takaful, and Islamic Fund contributed positively and significantly to the growth of IFSI. Sukuk (Islamic Bonds) acts as a stable source of long-term financing, Takaful enhances industry resilience through sharia-based risk mitigation, and Islamic Fund encourages sustainable investments that contribute to the expansion of Islamic financial markets. Regionally, the GCC and Southeast Asia regions show greater influence than other regions, driven by more mature regulations and more developed financial infrastructure. The findings provide important implications for regulators, investors, and financial institutions in designing policies and developing innovative Islamic finance products to enhance the sustainable growth of IFSI. In addition, this study provides a theoretical contribution by integrating the concepts of Capital Market Equilibrium Theory and Islamic Portfolio Theory in Islamic finance analysis. Thus, a deep understanding of the dynamics of Islamic financial instruments is essential in strengthening the Islamic financial ecosystem in the modern era.